Penerapan Media Papan Gambar dalam Meningkatkan Kemampuan Membaca Siswa Kelas 1 di MI Darul Ulum Bantaran - Nuryami Nuryami; Julia Setiowati; Mudmainah Mudmainah (FONDATIA, 2022)
The learning media used by teachers at MI Darul Ulum in improving students' reading skills, especially class I, still uses the syllable method so that students can only recognize letters and memorize some syllables. To overcome this, all researchers suggest using new media to improve students' reading skills. Drawing board media is media that consists of picture elements and can be disassembled with tools using small nails. These problems are discussed through Classroom Action Research (CAR) using two cycles. The results obtained from this study are that the use of drawing board media can improve the reading ability of MI Darul Ulum class 1 students with a total of 9 students. This can be proven from the significant increase in students' learning mastery and classical absorption from the two cycles that have been carried out, the indications are the increase in the average score of pre-cycle students, namely 58%, cycle I 72%, cycle II 83%. Likewise, the percentage of students' classical learning completeness also experienced a lot of improvement, namely 33% in the pre-cycle, 56% in the first cycle and 100% in the second cycle.